UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL dan FRAKSI DAUN SEMBUNG (Blumea balsamifera L.) TERHADAP BAKTERI Staphylococcus epidermidis - Sa'adah, Hayatus; Pristanti, Ragilia; Warnida, Husnul (Jurnal Riset Kefarmasian Indonesia, 2024)
Sembung Leaves (Blumea balsamifera L.) is a plant with many properties, one of which is antibacterial. Sembung leaves have several chemical compounds such as tannins, saponins, and flavonoids which function as antibacterials. This study aims to determine the diameter of inhibition zone, the value of Minimum Inhibition Concentration (MIC) dan the value of Minimum Bactericidal Concentration (MBC) of ethanol extract, n-hexane fraction, ethyl acetat fraction and water fraction of sembung leaves (Blumea balsamifera L.) against the staphylococcus epidermidis bacteria. Antibacterial testing by using disc diffusion dan solid dilution methods. Ethanol extract and fractions of sembung leaf (Blumea balsamifera L.) that has been obtained are diluted with a concentration of 10%, 25%, and 50%. The positive control as clindamycin 1% and DMSO as the negative control. The results showed that ethanol extract of sembung leaves (Blumea balsamifera L.) can inhibit the growth of Staphylococcus epidermidis bacteria at a concentration of 10% which is 8,1 mm, concentration of 25% which is 9,13 mm, concentration of 50% which is 10,1 mm. The n-hexane fraction can inhibit Staphylococcus epidermidis bacteria at a concentration of 10 % which is 6,1 mm, concentration of 25% which is 7,11 mm, concentrarion of 50% which is 7,21 mm. The ethyl acetate fraction can inhibit Staphylococcus epidermidis bacteria at a concentration of 10% which is 9,1 mm, concentration of 25% which is 11,16 mm, concentration of 50% which is 12,26 mm. The water fraction there is no inhibition zone diameter. The MIC of ethanol extract of sembung leaves is 10%, n-hexane fraction is 25% and ethyl acetate fraction is 10%. The MBC of ethanol extract was at a concentration of 25%, n-hexane fraction at a concentration of 50% and ethyl acetate fraction at a concentration of 10%.